Integration of Values in Serat Wulangreh with Pesantren’s Values in Building Professionalism of Ma’had Teachers - Ahmad Dahri; Muhammad Husni; Muhammad Adib (STAI Hubbulwathan Duri, 2023)
This research aims to introduce the idea of incorporating Serat Wulangreh's teachings and the ethos of Islamic boarding schools into the development of educators' professionalism as people and as professionals. A qualitative approach is used as a method in this study. The primary data source is the Serat Wulangreh book, with support from other literature data sources such as theories and scientific articles that discuss the values of pesantren or the values of the Serat Wulangreh, particularly in relation to teachers and their humanitarian attitudes. This study uses a data analysis technique called domain analysis. This is a step to see one variable as the research objective from the results of the coverage of two or three variables in general. So the result of this research is the epistemological concept of value integration that can build teacher professionalism.